Analisis Kemampuan Memahami Makna Konotasi dan Denotasi pada Siswa Kelas VI SD - Windu Tri Mukherna; Chandra Chandra; Inggria Kharisma (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The ability to understand denotative and connotative meanings is important in supporting the development of students' literacy and critical thinking skills in elementary schools. However, in practice, students still have difficulty in distinguishing the two types of meanings, especially in the context of connotative sentences that are figurative and require contextual interpretation. This study aims to analyze the ability of sixth grade elementary school students to identify and understand denotative and connotative meanings through various forms of questions, namely multiple choice, fill-in-the-blank, and descriptive, with a qualitative approach using the case study method. The steps of the case study include determining the focus of the study, literature review, case selection, data collection, data processing, data analysis, negotiation of results, and conclusions. The subjects of the study consisted of five sixth grade elementary school students who were analyzed based on their answers to the instruments that had been prepared. The results of the study showed that students had a good basic understanding of denotative and connotative meanings in explicit form. However, they still had difficulty in interpreting connotative meanings contextually and figuratively. The novelty of this study lies in the use of a contextual learning approach that is relevant to students' social and cultural lives, which has been proven to improve students' ability to understand meaning reflectively and critically.